Cudonia mongolica sp. nov. (Cudoniaceae, Rhytismatales) from Mongolia - Burenbaatar, G.; Chen, Zheng-Qing; Bau, Tolgor (Phytotaxa, 2025)
During an investigation of fungal species in Mongolia, some specimens with ascocarps growing on the humus layer accompanied by mosses were collected. Based on the ITS, LUS, RPB2 and TEF-1α fragments combined with morphological and molecular systematic studies, the fungus was identified as a new species of Cudonia, which is described and illustrated.